Construction of graphene oxide sheets based modified glassy carbon electrode (GO/GCE) for the highly sensitive detection of nitrobenzene. (4th July 2018) - Ahmad, Khursheed; Mohammad, Akbar; Ansari, Shagufi Naz; Mobin, Shaikh M
Abstract: Herein, we have demonstrated the role of simple graphene oxide (GO) sheets as electrocatalyst for the voltammetric detection of nitrobenzene (NBz). GO was synthesized from natural graphite flakes and characterized by PXRD, FE-SEM, FTIR and UV– vis spectroscopy. A binder free electrochemical sensor by modifying active surface area of glassy carbon electrode (GO/GCE ) was developed using simple drop casting method. The electrochemical behavior of the developed sensor towards NBz was examined extensively using cyclic voltammetry (CV), linear sweep voltammetry (LSV), differential pulse voltammetry (DPV) and square wave voltammetry (SWV). The modifiedGO/GCE sensor showed a limit of detection (LOD) of 66 nM by CV, 79 nM by LSV, 146 nM SWV and 135 nM and corresponding sensitivity of 157.14 μ A μ M −1 cm −2, 297.21 μ A μ M −1 cm −2, 677.14 μ A μ M −1 cm −2 and 1216.71 μ A μ M −1 cm −2 were observed by CV, LSV, DPV and SWV respectively.